The Influence of Self-Efficacy Beliefs in the Academic Performance of Latina/o Students in the United States: A Systematic Literature Review. Issue 2 (May 2018) - Manzano-Sanchez, Harold; Outley, Corliss; Gonzalez, Jorge E.; Matarrita-Cascante, David
This review had three aims: (a) examine the relationship between self-efficacy (SE) and academic performance (AP) in Latina/o students, (b) identify the types of measures of SE and AP that have been used, and (c) identify the differences between global and specific measures of SE in predicting academic performance in Latina/o students. Twenty-seven articles were included in the analysis. Major findings included the following: (a) significant and positive relationship between self-efficacy and academic performance in Latina/o students, at all educational levels, and through different types of measurements of self-efficacy and academic performance; (b) particular performance domains or content, or task-specific variables, were more favorable in the examination of the relationship between self-efficacy and academic performance than global domains; (c) Latina/o is not a homogeneous group; therefore, acculturation process, immigration status, family' experience on higher education, affective variables, and parents' and teachers' support were also factors that significantly correlated with Latina/os' academic achievement.